Practical Design and Application of a Flexible Structure using Object Oriented Programming - Lorena L., Paul (2001)
This article describes the development and implementation of new software uan flexible structure (Multiannillos), which handles information and abstract data. The paradigm of object-oriented programming (OOP) for practical application in written in C + + Prgrm for a cellular telephone device programming is used. The same structure can be used for other mobile devices such as wireless Handhelda etc.. requiring the use of new algorithms for efficient use of memory. The C / C + + language is used in a compiler Borland C + + 4.5